Computación evolutiva, una herramienta de modelamiento en cencias de la salud - Peláez-V., Alejandro; Villegas-T., Luisa Fernanda; Correa-M., Juan Carlos; Abad-M., Pablo (Revista Facultad de Odontología Universidad de Antioquia, 2020)
This article presents a review of the evolutive computation as an alternative of knowledge generation, exploring the basic concepts of this technique and, also, some applications in the Health Sciences. Some the most important aspects of the modelation of biological systems and processes are presented. These models can be used for making decisions in real life.